Actein Inhibits the Proliferation and Adhesion of Human Breast Cancer Cells and Suppresses Migration in vivo - Xiao-Xiao Wu; Grace Gar-Lee Yue; Grace Gar-Lee Yue; Jin-Run Dong; Christopher Wai-Kei Lam; Chun-Kwok Wong; Chun-Kwok Wong; Chun-Kwok Wong; Chun-Kwok Wong; Ming-Hua Qiu; Clara Bik-San Lau; Clara Bik-San Lau (Frontiers Media S.A., 2018)
Background and purpose: Metastasis is an important cause of death in breast cancer patients. Anti-metastatic agents are urgently needed since standard chemotherapeutics cannot diminish the metastatic rate. Actein, a cycloartane triterpenoid, has been demonstrated to exhibit anti-angiogenic and anti-cancer activities. Its anti-metastatic activity and underlying mechanisms were evaluated in the present study.Methods: The effects of actein on the proliferation, cell cycle phase distribution, migration, motility and adhesion were evaluated using two human breast cancer cell lines, MDA-MB-231 (estrogen receptor-negative) and MCF-7 cells (estrogen receptor-positive) in vitro. Western blots and real-time PCR were employed to examine the protein and mRNA expression of relevant signaling pathways. A human metastatic breast cancer cell xenograft model was established in transparent zebrafish embryos to examine the anti-migration effect of actein in vivo.Results:In vitro results showed that actein treatment significantly decreased cell proliferation, migration and motility. Furthermore, actein significantly caused G1 phase cell cycle arrest and suppressed the protein expression of matrix metalloproteinases of MDA-MB-231 cells. In addition, actein inhibited breast cancer cell adhesion to collagen, also reduced the expression of integrins. Actein treatment down-regulated the protein expression of epidermal growth factor receptor (EGFR), AKT and NF-κB signaling proteins. In vivo results demonstrated that actein (60 μM) significantly decreased the number of zebrafish embryos with migrated cells by 74% and reduced the number of migrated cells in embryos.Conclusion: Actein exhibited anti-proliferative, anti-adhesion and anti-migration activities, with the underlying mechanisms involved the EGFR/AKT and NF-kappaB signalings. These findings shed light for the development of actein as novel anti-migration natural compound for advanced breast cancer.